An Empirical Study on Internal and External Resources and the Performance of MSMEs in Misamis Oriental - Alonzo, Albert; Ganas, Estela (Journal of Interdisciplinary Perspectives, 2025)
Empirical investigations in Misamis Oriental are pretty limited in understanding the resources and performance of MSMEs. This study examined the internal resources—such as physical capital, financial resources, human capital, brand reputation, and organizational culture—as well as external resources, including relationships with suppliers, partners, and regulatory bodies, and the financial and non-financial performance of MSMEs. The study used a quantitative research design with a descriptive approach. It was conducted in the municipalities of Manticao, Lugait, and Naawan, located in the second legislative district of Misamis Oriental. The survey was carried out with 266 registered MSME owners or managers. Data was collected using a structured questionnaire administered directly through face-to-face interaction. Results indicate extensive utilization of physical capital and financial resources, resulting in operational efficiency and economic stability. The significant use of physical capital, financial resources, and brand reputation among MSMEs supports the Resource-Based Theory’s assertion that internal resources are essential for achieving superior performance. However, human capital was substantially underutilized, particularly in areas such as employee training, recruitment, and career development. The organizational culture also appeared to be in its early stages, with a limited emphasis on communication, employee engagement, and collaboration. On the other hand, external resources were notably underutilized. While some engagement was observed in supplier relationships, there was minimal involvement in broader strategic partnerships or regulatory interactions. This contrasts with the core premise of Resource Dependence Theory, which asserts that organizations rely on external entities for vital resources and that these dependencies significantly influence strategic decisions and operational behavior. The findings underscore the need to optimize internal resource utilization and strengthen external linkages. Additionally, government support must be relevant and accessible to bolster the performance of MSMEs effectively.